Soil Bacterial Communities From the Chilean Andean Highlands: Taxonomic Composition and Culturability - Maza, Felipe; Maldonado, Jonathan; Vásquez-Dean, Javiera; Mandakovic, Dinka; Gaete, Alexis; Cambiazo, Verónica; González, Mauricio (Frontiers in Bioengineering and Biotechnology, 2019)
The Atacama Desert is a highly complex, extreme ecosystem which harbors microorganisms remarkable for their biotechnological potential. Here, a soil bacterial prospection was carried out in the high Altiplano region of the Atacama Desert (>3,800 m above sea level; m a.s.l.), where direct anthropogenic interference is minimal. We studied: 1) soil bacterial community composition using high-throughput sequencing of the 16S rRNA gene and 2) bacterial culturability, by using a soil extract medium (SEM) under a factorial design of three factors: temperature (15 and 30 °C), nutrient content (high and low nutrient disposal) and oxygen availability (presence and absence). A total of 4,775 OTUs were identified and a total of 101 isolates were selected for 16S rRNA sequencing, 82 of them corresponded to unique or non-redundant sequences. To expand our view of the Altiplano landscape and to obtain a better representation of its microbiome, we complemented our Operational Taxonomic Units (OTUs) and isolate collection with data from other previous data from our group and obtained a merged set of OTUs and isolates that we used to perform our study. Taxonomic comparisons between culturable microbiota and metabarcoding data showed an overrepresentation of the phylum Firmicutes (44% of isolates versus 2% of OTUs) and an underrepresentation of Proteobacteria (8% of isolates versus 36% of OTUs). Within the Next Generation Sequencing (NGS) results, 33% of the OTUs were unknown up to genus, revealing an important proportion of putative new species in this environment. Biochemical characterization and analysis extracted from the literature indicated that an important number of our isolates had biotechnological potential. Also, by comparing our results with similar studies on other deserts, the Altiplano highland was most similar to a cold arid desert. In summary, our study contributes to expand the knowledge of soil bacterial communities in the Atacama Desert and complements the pipeline to isolate selective bacteria that could represent new potential biotechnological resources.